Preliminary results of a new antibiotic susceptibility test against biofilm installation in device-associated infections: the Antibiofilmogram®. Issue 6 (16th June 2016) - Tasse, Jason; Croisier, Delphine; Badel-Berchoux, Stéphanie; Chavanet, Pascal; Bernardi, Thierry; Provot, Christian; Laurent, Frédéric
Abstract : Biofilms are complex communities of microorganisms embedded in an extracellular matrix and adherent to a surface. The development was described as a four-stage process leading to the formation of a mature biofilm which was resistant to immune system and antibiotic actions. In bone and joint infections (BJIs), the formation of biofilms is a leading cause of treatment failure. Here we study the capacity of 11 antibiotics commonly used in the treatment of BJIs to inhibit the biofilm formation on 29 clinical Staphylococcus aureus isolates by a new test called Antibiofilmogram ® . The minimal inhibitory concentration (MIC) and biofilm MIC (bMIC) were determined in vitro and showed similar values for clindamycin, fusidic acid, linezolid and rifampin. Reversely, daptomycin, fosfomycin, gentamicin and ofloxacin showed a bMIC distribution different from MIC with bMIC above breakpoint. Finally, cloxacillin, teicoplanin and vancomycin revealed an intermediate bMIC distribution with a strain-dependent pattern. A murine in vivo model of catheter-associated S. aureus infection was made and showed a significant reduction, but not total prevention, of catheter colonization with cloxacillin at bMIC, and no or limited reduction with cloxacillin at MIC. Antibiofilmogram ® could be of great interest after surgical operations on contaminated prostheses and after bacteremia in order to prevent the colonization of the device. Abstract : Preliminary results of a new test called Antibiofilmogram ® able to identify the capacity of antibiotics to inhibit biofilm formation. Abstract :